2011
DOI: 10.1118/1.3609099
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of contrast‐enhanced whole brain radiotherapy on a CT scanner

Abstract: Contrast-enhanced total brain radiotherapy is feasible using a conventional CT tube with optimized dose application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…A CT also has been used in a clinical trial 50 after IV injection of rapidly clearing low molecular weight iodine contrast media. Monte Carlo modeling confirmed that standard CTs would be appropriate for human brain tumor therapy, especially with iodine loading 27 . Perhaps the most attractive method for practically using orthovoltage for deep tumors is provided by minibeam or microbeam technology.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A CT also has been used in a clinical trial 50 after IV injection of rapidly clearing low molecular weight iodine contrast media. Monte Carlo modeling confirmed that standard CTs would be appropriate for human brain tumor therapy, especially with iodine loading 27 . Perhaps the most attractive method for practically using orthovoltage for deep tumors is provided by minibeam or microbeam technology.…”
Section: Discussionmentioning
confidence: 80%
“…Significantly, the tumor-to-non-tumor ratio measured at 72 h was found to be 19.8:1. The Dose Enhancement Factor (DEF) was estimated from the percent iodine in the tumor based on previous Monte Carlo treatments 26,27 . Although approximate, values hitting as high as 4.5% iodine in the peripheral rim of the tumor indicate that the radiation dose delivered there may be multiplied by a factor of 8.…”
Section: Resultsmentioning
confidence: 99%
“…CT scanners are the standard imaging technique for diagnosis and treatment planning in virtually all cancer centres [49] and are increasingly replacing traditional simulator units for radiotherapy treatment planning. It is even possible to modify a conventional CT scanner to deliver therapeutic X-ray doses using iodine CERT [12,50]. This treatment modality produces dose distributions similar to those obtained with 10 MV megavoltage therapy [12] and enables combined imaging, simulation, and treatment with the same machine.…”
Section: Nanoparticles For Dual-mode Imaging and Therapy?mentioning
confidence: 99%
“…[4][5][6] Since about three decades ago, techniques based on this concept have been introduced, through both theoretical and experimental studies using dosimetry measurements in phantoms and animal models, as well as Monte Carlo simulations. [7][8][9][10][11] Concerns have also been raised regarding the use of iodinated contrast in diagnostic radiological examinations on both microdosimetric and dosimetric levels. 6 On the microdosimetric level, the presence of iodinated contrast agents has been proven to cause chromosome damage and amplifies DNA radiation damage in CT (kilovolt x-rays).…”
Section: Introductionmentioning
confidence: 99%